Access to antiretroviral drugs and AIDS management in Senegal - (:unkn) unknown (My University, 2003)
Objectives Description and analysis of the Senegalese Antiretroviral Drug Access Initiative (ISAARV), the first governmental highly active antiretroviral therapy (HAART) treatment programme in Africa, launched in 1998.Methods and results ISAARV was initially an experimental project designed to evaluate the feasibility, efficacy and acceptability of HAART in an African context. It was based on four principles: collective definition of the strategy, with involvement of the health professionals who would be called on to execute the programme; matching the objectives to available means (gradual enrollment according to drug availability); monitoring by several research programmes; and ongoing adaptation of treatment and follow-up according to the latest international recommendations.Persons qualifying for antiretroviral (ARV) therapy are selected on the basis of immunological and clinical criteria, regardless of economic and social considerations. A system of subsidies was created to favor access to ARV. Following the ARV price reductions that occurred in November 2000, 100% subsidies were created for the poorest participants. Optimal adherence was ensured by monthly follow-up by pharmacists and support groups held by social workers and patient associations. The chosen supply and distribution system allowed drug dispensing to be strictly controlled.Conclusion The ISAARV programme demonstrates that HAART can be successfully prescribed in Africa. This experience has served as the basis for the creation of a national treatment programme in Senegal planned to treat 7000 patients by 2006.
Keywords: African Research